Longer-Term Postcure Measurement of Cuspal Deformation Induced by Dimensional Changes in Dental Materials - A. Falsafi; J. D. Oxman; P.-H. Tse; T. T. Ton (International Journal of Dentistry)
Aim. This paper presents a simple, versatile in vitro methodology that enables indirect quantification of shrinkage and expansion stresses under clinically relevant conditions without the need for a dedicated instrument. Methods. For shrinkage effects, resulting cusp deformation of aluminum blocks with MOD type cavity, filled with novel filling compositions and commercial cements, has been measured using a bench-top micrometer and a Linear Variable Differential Transformer (LVDT, a displacement transducer) based instrument. Results. The results demonstrated the validity of the proposed simple methodology. The technique was successfully used in longer-term measurements of shrinkage and expansion stress for several dental compositions. Conclusions. In contrast to in situ techniques where a measuring instrument is dedicated to the sample and its data collection, the proposed simple methodology allows for transfer of the samples to the environment of choice for storage and conditioning. The presented technique can be reliably used to quantify stress development of curing materials under clinically relevant (oral) conditions. This enables direct examination and comparison of structural properties corresponding to the final stage of formed networks. The proposed methodology is directly applicable to the study of self-curing systems as they require mouth-type conditions (temperature and humidity) to achieve their designed kinetics and reactions.